A Discourse Analysis of Cohesion Devices an Students’ Writing of Recount Text - Tungky Ariwibowo; Didin Nuruddin Hidayat; Nida Husna; Alek Alek; Agus Sufyan (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aimed to determine the types of cohesive devices utilised in the recount text writing of Tenth-grade students at MAN Huta Godang during the academic year 2022/2023 and to identify the most prevalent form of cohesive device. The data was taken from 5 students writing. The study employed a qualitative descriptive method that includes cohesive devices in students' writing. It was found that the types of grammatical cohesion were reference, conjunction, and ellipsis. The most frequently used type of grammatical cohesion is the reference. Students who recount text writing using grammatical cohesion can be in the "fair" category with a percentage of 30.2%. The study suggests students should be aware that merely including a large number of cohesive elements in an essay does not guarantee that the essay will demonstrate or even produce cohesiveness; rather, the cohesive elements must be used in a logical and consistent manner throughout the text. Keywords: Discourse Analysis, Cohesive Devices, Recount Text.